Pengaruh Brand Developer dan Lokasi Properti Terhadap Keputusan Pembelian Konsumen di Apartemen Victoria Square Tanggerang - Hindun Hulopi; Tongam Sirait (Publikasi Indonesia, 2025)
This study aims to analyze the influence of brand developer and property location on consumer purchasing decisions at Victoria Square Tanggerang Apartment. Along with the rapid development of the property industry, understanding the factors that influence purchasing decisions has become very important for property industry players. This research uses a quantitative approach with survey methods on 64 respondents who plan to purchase apartment units at Victoria Square Tanggerang. Data were collected through questionnaires and analyzed using multiple linear regression techniques with SPSS version 27 software. The results showed that brand developer has a positive and significant effect on consumer purchasing decisions with a regression coefficient of 0.228 and a significance value of 0.000 (p < 0.05). Property location also shows a positive and significant influence with a regression coefficient of 0.472 and a significance value of 0.000 (p < 0.05). Simultaneously, brand developer and property location have a significant effect on consumer purchasing decisions as evidenced by the F test with an F value of 90.690 and a significance value of 0.000 (p < 0.05). These findings indicate that consumers give high consideration to developer reputation and strategic property location in making purchasing decisions. The combination of a trusted brand developer and strategic property location creates a strong value proposition for consumers, thereby increasing the probability of apartment purchasing decisions.